SYNONYMS IN ACTION: A CASE STUDY - Clift, Rebecca (International Journal of English Studies, 2003)
This paper discusses what the methods of conversation analysis (CA) might have to offer the study of linguistic synonymy. It takes as a case study two items commonly held to be synonyms -'actually' and 'in fact'- and shows considerable differences between the two in their interactional implementation: they are implicated in the prosecution of differing courses of action. Such cases argue that it is analytically more profitable to consider what a lexical item does in the context of talk than what it means.